2007
DOI: 10.1097/hjh.0b013e3282b9720e
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene polymorphism predicts the time-course of blood pressure response to angiotensin converting enzyme inhibition in the AASK trial

Abstract: Objective-It has yet to be determined whether genotyping at the angiotensin-converting enzyme (ACE) locus is predictive of blood pressure response to an ACE inhibitor.Methods-Participants from the African American Study of Kidney Disease and Hypertension trial randomized to the ACE inhibitor ramipril (n = 347) were genotyped at three polymorphisms on ACE, just downstream from the ACE insertion/deletion polymorphism (Ins/Del): G12269A, C17888T, and G20037A. Time to reach target mean arterial pressure (≤ 107 mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…[19] This SNP was associated with two other variants, rs4341, and rs4344 that influence drug therapy for Fluvastatin, Thiazides, Furosemide, Spironolactone, Pravastatin, and Ramipril respectively. [20][21] [22] These drugs, especially Fluvastatin, are prescribed for hypercholesterolemia and for prevention of cardiovascular diseases. [23] For the gene MIA3, with the sole SNP variant association of variants rs10495197 and rs17163303, it was found that each of the SNPs individually has the potential to influence the drug therapy for Vancomycin.…”
Section: Pharmacogenetic Implication Studymentioning
confidence: 99%
“…[19] This SNP was associated with two other variants, rs4341, and rs4344 that influence drug therapy for Fluvastatin, Thiazides, Furosemide, Spironolactone, Pravastatin, and Ramipril respectively. [20][21] [22] These drugs, especially Fluvastatin, are prescribed for hypercholesterolemia and for prevention of cardiovascular diseases. [23] For the gene MIA3, with the sole SNP variant association of variants rs10495197 and rs17163303, it was found that each of the SNPs individually has the potential to influence the drug therapy for Vancomycin.…”
Section: Pharmacogenetic Implication Studymentioning
confidence: 99%
“…The pharmacogenetic value of the ACE alleles is that the outcomes of these HF treatments can be predicted according ACE genotype (McNamara et al, 2001;McNamara et al, 2004). It was suggested that blood pressure response to ACE inhibitors can be predicted according to the ACED/I genotype (Bhatnagar et al, 2007). However further studies showed that blood pressure response variability to ACE inhibitors is due to a complex polygenic effect of other RAAS polymorphisms, and are not only angiotensin gene related (Pilbrow et al, 2007;Su et al, 2007).…”
Section: Angiotensin-converting Enzyme Pharmacodynamicsmentioning
confidence: 99%
“…35 Molecular heterosis (more extreme phenotype for heterozygotes than either homozygote class, sometimes called "overdominance") was noted in a study of ACE locus polymorphisms on response to ACE inhibition in hypertension. 54 Detection of heterosis explicitly requires analysis of diploid genotype (rather than simply allele) effects on a trait. 55 To assess the genotype effect of the ACE locus on ACE inhibitor responsiveness, hypertensive patients in the African American Study of Kidney Disease and Hypertension trial (AASK) taking ACE inhibitor ramipril were genotyped at 3 intronic polymorphisms spanning the biologically active regions of the ACE locus.…”
Section: Cardio-renal Target Organ Susceptibility Genes and Hypertensionmentioning
confidence: 99%
“…60 As noted above under genetic complexity, black hypertensive patients with ACE homozygous genotypes at G12269A (or haplotypes) responded to ramipril significantly faster than those with a heterozygous genotype or haplotype. 54 …”
Section: Pharmacogenetics: Antihypertensive Drugsmentioning
confidence: 99%